2017
DOI: 10.1038/s41598-017-11430-7
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Improves Endothelial Function and Reduces Blood Pressure in Diabetic Spontaneously Hypertensive Rats Independent from Glycemia Control: Comparison to Vildagliptin

Abstract: Metformin confers vascular benefits beyond glycemia control, possibly via pleiotropic effects on endothelial function. In type-1-diabetes-mellitus (T1DM-)patients metformin improved flow-mediated dilation but also increased prostaglandin(PG)-F2α, a known endothelial-contracting factor. To explain this paradoxical finding we hypothesized that metformin increased endothelial-vasodilator mediators (e.g. NO and EDHF) to an even larger extent. Spontaneously-hypertensive-rats (SHR) display impaired endothelium-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 57 publications
2
28
0
1
Order By: Relevance
“…Lower values of VEGF-A in a combination of hypertension with T2DM versus isolated AH may be explained by the fact that in the present study, all patients with T2DM at the time of inclusion received Metformin. At present, there are numerous data, including those obtained in randomized trials, concerning the beneficial effects of Metformin on the function of endothelium [14]. Thus, Wu S et al (2014) demonstrated that the use of Metformin over a period of 12 months resulted in a significant improvement in endothelium function [15].…”
Section: Discussionmentioning
confidence: 99%
“…Lower values of VEGF-A in a combination of hypertension with T2DM versus isolated AH may be explained by the fact that in the present study, all patients with T2DM at the time of inclusion received Metformin. At present, there are numerous data, including those obtained in randomized trials, concerning the beneficial effects of Metformin on the function of endothelium [14]. Thus, Wu S et al (2014) demonstrated that the use of Metformin over a period of 12 months resulted in a significant improvement in endothelium function [15].…”
Section: Discussionmentioning
confidence: 99%
“…Even the antimalaric agents chloroquine and hydroxychloroquine, initially proposed as a therapy for COVID-19 based on anecdotal data [229,236], have been shown to improve endothelial function [237,238]. If our theory is correct [239], other drugs that might be effective in treating COVID-19 patients through their beneficial effects on endothelial cells include α1 adrenergic receptor blockers (e.g., doxazosin) [240], modulators of Sigma receptors [241][242][243], metformin [244], indomethacin [245], and endothelin receptor antagonists (e.g., bosentan) [246]. However, data from randomized trials confirming the actual efficacy of these drugs are not (yet) available.…”
Section: Anticoagulation As a Key Therapy For Covid-19mentioning
confidence: 99%
“…Metformin raises the tissue concentration of hydrogen sulphide (H 2 S), which is an atheroprotective gasotransmitter (Hamidi Shishavan, et al, 2017;Xu, Liu, & Liu, 2014). H 2 S functions as a vasculoprotective factor by sulfhydrating potassium channels and acting as an EDHF (Félétou M. , 2011).…”
Section: The Biguanide Anti-hyperglycaemic Agent Metforminmentioning
confidence: 99%